Emerging carbon-based flexible anodes for potassium-ion batteries: Progress and opportunities - Li, Wenbin; Yang, Zihao; Zuo, Jiaxuan; Wang, Jingjing; Li, Xifei (Frontiers in Chemistry, 2022)
In recent years, carbon-based flexible anodes for potassium-ion batteries are increasingly investigated owing to the low reduction potential and abundant reserve of K and the simple preparation process of flexible electrodes. In this review, three main problems on pristine carbon-based flexible anodes are summarized: excessive volume change, repeated SEI growth, and low affinity with K+, which thus leads to severe capacity fade, sluggish K+ diffusion dynamics, and limited active sites. In this regard, the recent progress on the various modification strategies is introduced in detail, which are categorized as heteroatom-doping, coupling with metal and chalcogenide nanoparticles, and coupling with other carbonaceous materials. It is found that the doping of heteroatoms can bring the five enhancement effects of increasing active sites, improving electrical conductivity, expediting K+ diffusion, strengthening structural stability, and enlarging interlayer spacing. The coupling of metal and chalcogenide nanoparticles can largely offset the weakness of the scarcity of K+ storage sites and the poor wettability of pristine carbon-based flexible electrodes. The alloy nanoparticles consisting of the electrochemically active and inactive metals can concurrently gain a stable structure and high capacity in comparison to mono-metal nanoparticles. The coupling of the carbonaceous materials with different characteristics can coordinate the advantages of the nanostructure from graphite carbon, the defects and vacancies from amorphous carbon, and the independent structure from support carbon. Finally, the emerging challenges and opportunities for the development of carbon-based flexible anodes are presented.